105 Non-Invasive Measurements of Hemodynamic Transition at Birth. (October 2012) - Vonderen, JJ van; Roest, AA; Siew, ML; Walther, FJ; Hooper, SB; Pas, AB te
Abstract : Objective: To investigate the hemodynamic changes during transition at birth obtaining non-invasive physiological data in healthy term infants. Methods: In 18 newborns (GA 39 weeks (38–39)) born by a caesarian section; arterial oxygen saturation (SaO2 ) (preductally), heart rate (HR) and non-invasive blood pressure (BP) were measured and echocardiography using M-mode and Doppler flow was performed at 2, 5 and 10 minutes after birth. Results: Oxygen saturation and HR were within recommended target ranges. Mean BP did not change between measurement intervals (55 mm Hg at 2 min, 54 mm Hg at 5 min. and 54 mm Hg at 10 min) and was similar as BP measured at day 1. Left ventricle output (LVO) significantly increased between 2 min and 5 min (120.3 mL/kg/min (35.1) vs. 167.4 mL/kg/min (67.3); p value <0.001) but remained stable by 10 min (189.2 mL/kg/min (26.2); ns). The increase in LVO was significantly correlated to an increase in HR and left ventricle end diastolic diameter (14.3 mm at 2 min, 16.0 mm at 5 min and 16.6 mm at 10 min; p<0.001). We observed a bidirectional ductal flow in the first minutes, but large inspirations following a cry overruled the bidirectional ductal flow causing a large left to right shunting. Conclusion: At birth, the most significant hemodynamic change occurred in the first 5 minutes whereby an increase in preload and heart rate increased LVO. Inspirations had a major influence on ductal flow, causing large left to right shunting. Blood pressure at birth remained stable.